Effect of water–fog particle size on dust fall efficiency of mechanized excavation face in coal mines. (1st May 2020) - Fang, Xueming; Yuan, Liang; Jiang, Bingyou; Zhu, Wenjun; Ren, Bo; Chen, Minggong; Mu, Min; Yu, Guofeng; Li, Peng
Abstract: Respiratory dust and dust fall from the mechanized excavation faces of coal mines are crucial issues that require immediate attention. The dust fall technique for two-phase gas–water spraying is effective in solving these issues. We designed a spray dust fall simulated experimental system to test the dust fall efficiency for six grain sizes of water mist: D50 = 9.00 μm, 18.75 μm, 29.87 μm, 49.85 μm, 75.85 μm, and 116.47 μm, respectively. The results demonstrate that the smaller the D50 of the water mist particles, the better is the trapping effect of the respiratory dust. The main dust catching stage of water mist of different particle sizes is different. The main dust catching stage of water mist of small particle size is the initial contact stage of mist particles and respirable dust, while the main dust catching stage of water mist of large particle size appears later. The research findings will lay a theoretical groundwork for the application of new-type nozzle in the coal mines and provide technical support to the clean production of the coal mines. Highlights: Effect of water-fog particle size on dust fall efficiency was studied. A new respiratory dust mitigation of gas-water spraying was studied. Dust mitigation system has been tested successfully in rock heading face.